Do economic conditions influence union activism behaviour?. (May 2017) - Angrave, David; Charlwood, Andy; Greenwood, Ian
This article develops and tests the theory that union activism is related to economic conditions using a nationally representative panel of workers from the UK. Results suggest that a fall in real wages of two percentage points and a three percentage point increase in the unemployment rate are both associated with a one-tenth increase in the probability that a 'benchmark' worker will become a union activist (albeit from a low base). This relationship is largely explained by the behaviour of workers in highly unionized sectors.